Educação sexual: perspectivas de estudantes de graduação de psicologia e pedagogia - Alvaro, Daniela de Camargo (2018)
Although sexuality is present in every dimension of the human being, it is still surrounded by a lack of knowledge in several areas. Therefore, sexual education, like all teaching-learning activities on human sexuality, should include knowledge about basic information, discussions and reflections on values, norms, feelings, emotions and attitudes related to sexual life. Objective: to raise the acquisition of knowledge and the perception undergraduate students in psychology and pedagogy have about sexuality and sex education. Method: Participants were students enrolled in a private college, and the data were collected using the Sociodemographic Identification Questionnaire, Attitude Questionnaire for Sexual Education in Students and the Questionnaire for Assessment of Teachers' Attitudes towards Sexual Education - QAAPES. This is a descriptive quantitative study of the exploratory type. Results: Of the 378 participants, 335 (88.6%) were female and 43 (11.4%) were males, aged between 17 and 62 years. With regard to attitudes towards sex education, 213 participants agreed that sex education should be made available in schools and be a shared responsibility with parents, and 161 (83.5%) responded that they should start teaching Fundamental II. The topics that should be part of the sexual education curriculum were STD / AIDS, sexual abuse, contraception, gender and diversity, family settings and reproduction. Regarding the involvement in sexual education, 39 (16.5%) Psychology students and 35 (72.9%) Pedagogy had some training in class or stage. There was a lack of positive attitude on the part of the students regarding sex education, as well as comfort to talk about some subjects. Of the total number of students in both courses, 172 intend to develop sex education activities. Conclusion: All students brought a model of sexual education based on the biological and hygienist approach, leaving aside the emancipatory approach that works the social formation of the individual. It is necessary to invest in training aimed at comprehensive sexual education in all aspects of the human being: biological, psychological, sociocultural, historical, ethical, considering the multiple forms of pleasure and sexual satisfaction, which contributes to the formation of sensitive, and able to work in sex education.